The Effect of Competency And Locus of Control On Accounting Student's Jobreadiness - Muhammad Ratal Ratal; Nuramalia Hasanah; Adam Zakaria (Jurnal Akuntansi, Perpajakan dan Auditing, 2022)
This study examined the impact of accounting students' ethical competence, knowledge competence, ability  competence,  relationship  competence,  analytical  competence,  and  locus  of  control  on  their job-readiness. This study utilizes primary data in the form of a questionnaire distributed to accounting students  in  the  UNJ  Faculty  of  Economics.  This  study's  population  consisted  of  undergraduate accounting students who were eligible to enrollin thesis courses and were still participating in odd semester lectures for the academic year 2021/22. This study's sample selection employed a technique of  purposive  sampling  and  yielded  a  study  sample  of  100  respondents.  This  research  employs quantitative methods. Descriptive statistical analysis and multiple linear regression analysis are used for analysis. This study's findings indicate that ethical competence, knowledge competence, ability competence, relationship competence, and locus of control positively influence accounting students' job-readiness. Meanwhile, analytical ability has no bearing on accounting students' work readiness.